Continuous hydrothermal synthesis of inorganic nanoparticles - Evans, Edward (2006)
In Chapter 1, the special properties of nanoparticles are discussed, followed by different methods of nanoparticle synthesis, particularly the hydrothermal flow synthesis. Finally, factors thought to affect particle size are identified, and the aims of the Thesis are stated.